Risco de violência e suporte social de pessoas adultas e idosas com doença renal crônica em tratamento hemodialítico - Modesto, Bruna Giovana (2024)
Chronic Kidney Disease (CKD) is a clinical condition that involves the progressive and irreversible loss of kidney function. This can be a risk factor for the early development of frailty and generate profound care needs. Dependence on caregivers, associated with health comorbidities, have been pointed out as indicators of greater exposure to abuse, neglect, and violence. The objective of this study was to verify the risk of violence in people with CKD undergoing hemodialysis and its relationship with social support, family composition, depression, frailty, and functionality. This is a concomitant mixed-methods study, which was carried out with elderly and adults linked to a Renal Replacement Therapy Unit (UTRS) located in a city in the interior of the State of São Paulo. Qualitative and quantitative instruments were applied concomitantly to collect data, including: semi-structured interview, Patient Health Questionnaire-9 (PHQ-9), Medical Outcomes Study (MOS) Social Support Scale, Genogram and Ecomap, Katz and Lawton Index, Vulnerability Abuse Screening Scale (VASS), Tilburg Frailty Indicator (TFI). The convenience sample included 89 participants aged 40 or over, with more than six months of treatment and with understanding and communication skills, according to the results indicated by the Mini-Mental State Examination. Of the participants, the majority were women (46 (51%) and 43 (48%) were men, with an average age of 62 years, ranging from 41 to 85 years. Women reported suffering violence in greater numbers than men. Regarding education, a higher frequency of risk and violence committed was observed in people with 5 or more years of education. It was observed that violence is more frequent among adults aged 40 to 59 years and elderly individuals aged 60 to 69 years, compared to older elderly individuals. Statistical analysis revealed that depression, functionality in instrumental activities of daily living, frailty and social support presented significant relationships with the risk of violence. In the multivariate analysis, using the forward criterion, the variables depression, frailty and sex were significantly associated with the risk of violence. Patients with moderately severe depression are 5.8 times more likely to suffer violence (OR = 5.847; p = 0.049), while frail individuals are 6.5 times more likely (OR = 6.525; p = 0.017) to be victims of violence compared to non-frail individuals. The present study contributes to new fronts of work focused on longevity and biopsychosocial issues.